Acción terapéutica de los ácidos aminados hematógenos: triptofano e histidina - Echave, Dionisio (1941)
The author describes the importance of “aminados” acids as essential proteins constituents and points out in a special way how triptofano and histidina lack, contributes to haemoglobin and red and white globules descention. Experimentally he proves in several clinical tableaux of anaemias of different origin, the improvement of the sanguineous tableau by “aminada” therapeutic (triptofano and histidina).